The wild parrots of Telegraph Hill [videorecording (DVD)]. - Bittner, Mark (Docurama : Distributed by New Video, 2008)
This wonderful film tells the true story of a local bohemian, Mark Bittner and his remarkable relationship with a flock of wild parrots. Follows the ups-and-downs of these wild birds that reside within the green nooks of San Francisco where Bittner befriends, feeds and names the members of the flock.